2005
DOI: 10.1194/jlr.r400012-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Thematic review series: The Pathogenesis of Atherosclerosis. An interpretive history of the cholesterol controversy: part II:the early evidence linking hypercholesterolemia to coronary disease in humans

Abstract: The first in this series of historical reviews dealt with the pioneering animal model work of Anitschkow, implicating blood cholesterol in the pathogenesis of atherosclerosis, and the pivotally important work of Gofman, providing evidence that lipoprotein-bound cholesterol was a major factor in the human disease. This second installment reviews the early lines of evidence linking hypercholesterolemia in humans to the progression of atherosclerosis and the risk of coronary heart disease. The argument is made th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(87 citation statements)
references
References 60 publications
1
78
0
8
Order By: Relevance
“…As early as 1970, many of the country's experts in atherosclerosis and preventive cardiology, and the American Heart Association, were already convinced that there was a causal connection between blood cholesterol and coronary heart disease, as discussed in the earlier installments of this series (1)(2)(3). However, no one could be certain how firm that connection was or how much impact treatment to decrease cholesterol levels would have.…”
mentioning
confidence: 98%
“…As early as 1970, many of the country's experts in atherosclerosis and preventive cardiology, and the American Heart Association, were already convinced that there was a causal connection between blood cholesterol and coronary heart disease, as discussed in the earlier installments of this series (1)(2)(3). However, no one could be certain how firm that connection was or how much impact treatment to decrease cholesterol levels would have.…”
mentioning
confidence: 98%
“…Hypercholesterolemia in humans has been shown to play a major role in atherosclerosis, cardiovascular disease, including coronary heart disease and stroke as well as cerebrovascular diseases [2][3][4]. High cholesterol has also been associated with an increased risk of metabolic syndrome symptoms, including abdominal obesity (large waist circumference), hyperglycemia, hypertriacylglycerolemia and hypertension by as much as 3-fold [5].…”
Section: Introductionmentioning
confidence: 99%
“…The theory that an increased dietary intake of saturated fats and cholesterol results in an increase in serum total cholesterol and LDL cholesterol-and therefore an increase in the risk of heart disease-has been accepted since the Framingham Heart Study (9). The study reported that high serum cholesterol was a major risk factor for coronary artery disease (CAD) (10).…”
Section: History Of the Dietary Guidelines And Current Status: The Famentioning
confidence: 89%